Socio Cultural Study of Communities for Biodiversity Conservation - Tutut Sunarminto (Department of Forest Resources Conservation and Ecotourism - IPB University, 1993)
An understanding of human behaviour is one of the key factors for a successful biodiversity conservation, because man is the major subject in natural resources management. Human ecology andrural sociology help to reveal more about human behaviour to support biodiversity conselvation of natural rcsources.